Analytical framework for integrating climate change mitigation and adaptation in local urban planning policy - Kiranmayi Raparthi (Revista Iberoamericana de Estudios de Desarrollo)
Climate change is a multidimensional observable fact and is regarded as one of the greatest challenge human societies is facing in the 21st century. Debates on climate change advocate that urban areas not only contribute to climate change by emitting huge amounts of carbon-dioxide gas into the atmosphere, but also play a vital role in addressing climate change. This research investigates whether local urban planning policies in master plans target climate change mitigation and adaptation. Accordingly, this research undertook a qualitative content analysis of the policy framework of master plans that are involved in the sample and developed climate change mitigation indexes for all the sampled master plans by assessing urban policies against climate change mitigation evaluation protocols. This research significantly contributes to the field of urban planning and public policy by developing empirical evidence that analyzes the relationship between urban planning policies and climate change mitigation and adaptation. This research supports the use of master plans as an effective tool in mitigating and adapting to climate change and has an implication for mainstreaming climate change mitigation and adaptation in urban planning.